Hygro-mechanical model for concrete pavement with long-term drying analysis - Jakub Veselý; Vít Šmilauer (Acta Polytechnica CTU Proceedings, 2023)
Concrete pavements are subjected to the combination of moisture transport, heat transport and traffic loading. A hygro-mechanical 3D finite element model was created in OOFEM software in order to analyse the stress field and deformed shape from a long-term non-uniform drying. The model uses a staggered approach, solving moisture transfer weakly coupled with MPS viscoelastic model for ageing concrete creep and shrinkage. Moisture transport and mechanical sub-models are calibrated with lab experiments, long-term monitoring on D1 highway and data from 40 year old highway pavement. The slab geometry is 3.5×5.0×0.29 m, resting on elastic Winkler-Pasternak foundation. The validation covers autogenous and drying strain on the slab. The models predict drying-induced tensile stress up to 3.3 MPa, inducing additional loading on the slab, uncaptured by current design methods.